2006
DOI: 10.1210/en.2005-0518
|View full text |Cite
|
Sign up to set email alerts
|

Osteostat/Tumor Necrosis Factor Superfamily 18 Inhibits Osteoclastogenesis and Is Selectively Expressed by Vascular Endothelial Cells

Abstract: Vascular endothelial cells (EC) participate in the process of bone formation through the production of factors regulating osteoclast differentiation and function. In this study, we report the selective expression in primary human microvascular EC of Osteostat/TNF superfamily 18, a ligand of the TNF superfamily. Osteostat protein is detectable in human microvascular EC and is highly up-regulated by IFN-alpha and IFN-beta. Moreover, an anti-Osteostat antibody strongly binds to the vascular endothelium in human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
0
14
1
1
Order By: Relevance
“…Recruitment of proinflammatory cells is important for the development of inflammation and cell recruitment is deficient in GITR −/‐ mice. High levels of GITRL expression have been detected in ECs and, in particular, in microvascular‐derived ECs 33 . However, we did not find GITRL expression in ECs of normal untreated mice (.…”
Section: Gitr/gitrl System In Lung Inflammation: Cellular and Moleculcontrasting
confidence: 67%
“…Recruitment of proinflammatory cells is important for the development of inflammation and cell recruitment is deficient in GITR −/‐ mice. High levels of GITRL expression have been detected in ECs and, in particular, in microvascular‐derived ECs 33 . However, we did not find GITRL expression in ECs of normal untreated mice (.…”
Section: Gitr/gitrl System In Lung Inflammation: Cellular and Moleculcontrasting
confidence: 67%
“…In short, bone marrow cells obtained from tibia of 8-to 10-week-old female C57BL/6 mice were cultured in a-minimal essential medium (MEMa) containing 10% FBS for [16][17][18][19][20] …”
Section: Cell Culturementioning
confidence: 99%
“…Endothelin-1 also nteracts with osteoclast precursors, leading to cell motility and osteoclastic bone resorption [16]. Tumor necrosis factor superfamily member 18 which is produced by vascular endothelial cells inhibits osteoclastogenesis [17], whereas endothelial progenitor cells enhance their survival, migration and differentiation [18]. Moreover, Chikatsu et al have recently shown that the formation of tartrate-resistant acid phosphatase (TRAP)-positive cells was suppressed, when bone-derived clonal endothelial cells were separately co-cultured with bone marrow macrophages by a membrane filter in a Transwell [19], suggesting that a soluble inhibitory factor(s) of osteoclast differentiation is produced by vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…(Tumor necrosis factor recpertor superfamily member 18, [13] 。Leetal 等报道了活动性的系统性红斑 狼疮患者体内的 GITR 的表达量比非活动性的患者要 高 [14] 。I 型糖尿病的患儿与正常的对照组相比,T 调 节细胞上表现出 GITR-mRNA 表达量的减少 。高表达量的 GITRL 在上皮细胞中检测到, 尤其是在微血管来源的上皮细胞 [16] 。但 GITRL 比较…”
Section: Gitr/gitrl 信号通路与支气管哮喘的研究进展unclassified